ASSESSMENT OF PAIN AND BLEEDING IN THE FIRST POSTOPERATIVE DAY FOLLOWING COBLATION TONSILLECTOMY - Rafid Jabbar Almaidi (Basrah Journal of Surgery, 2020)
There are different techniques for tonsillectomy other than traditional such as; cold steel technique, bipolar diathermy, and nowadays the new plasma technology which is known as coblation (controlled ablation) tonsillectomy. This study aimed to assess the first 24 hours postoperative pain and bleeding after coblation tonsillectomy. Fifty patients aged between 4-10 years who underwent coblation tonsillectomy were included in this prospective descriptive study, the main indications for tonsillectomy were; recurrent tonsillitis and obstructive sleep apnoea. The results showed that no bleeding at all within the first 24 hours with significant reduction in feeling of pain after. In conclusion, coblation tonsillectomy is a promising technique to perform tonsillectomy.